2019
DOI: 10.1029/2019jc015140
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Biogeochemical Controls on pH Dynamics in the Northern Gulf of Mexico During Summer Hypoxia

Abstract: High‐accuracy spectrophotometric pH measurements were taken during a summer cruise to study the pH dynamics and its controlling mechanisms in the northern Gulf of Mexico in hypoxia season. Using the recently available dissociation constants of the purified m‐cresol purple (Douglas & Byrne, 2017, https://doi.org/10.1016/j.marchem.2017.10.001; Müller & Rehder, 2018, https://doi.org/10.3389/fmars.2018.00177), spectrophotometrically measured pH showed excellent agreement with pH calculated from dissolved inorganic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 98 publications
2
21
0
Order By: Relevance
“…Our result for the dominance of upwelling over mixing in driving pH fluctuations is consistent with a related hypoxia modeling study in which Scully (2010) showed that wind-driven lateral upwelling and ventilation of deep hypoxic water onto shallow shoals are more important than wind mixing in supplying dissolved oxygen to the bottom water. This is probably more so for CO 2 than for O 2 as the air-sea gas exchange flux is generally much smaller for CO 2 than for O 2 (Jiang et al, 2019).…”
Section: Discussionmentioning
confidence: 98%
“…Our result for the dominance of upwelling over mixing in driving pH fluctuations is consistent with a related hypoxia modeling study in which Scully (2010) showed that wind-driven lateral upwelling and ventilation of deep hypoxic water onto shallow shoals are more important than wind mixing in supplying dissolved oxygen to the bottom water. This is probably more so for CO 2 than for O 2 as the air-sea gas exchange flux is generally much smaller for CO 2 than for O 2 (Jiang et al, 2019).…”
Section: Discussionmentioning
confidence: 98%
“…In productive coastal zones, algae and other biogenic particles decompose in subsurface waters. Their respiration and/or remineralization processes consume dissolved oxygen (DO) and release a great deal of CO 2 into subsurface waters, leading to more rapid seawater acidification in coastal seas, compared with the open ocean (Feely et al, 2010;Cai et al, 2011;Melzner et al, 2013;Jiang et al, 2019). Moreover, the respirationinduced seasonal acidification is subject to uneven distributions of seawater temperature, salinity and alkalinity in coastal seas.…”
Section: Introductionmentioning
confidence: 99%
“…The DIC and TA data from 2017 are reported herein. Data previously analyzed and reported include pH and DO data from 2006–2010 and 2017 (Cai et al, 2011; Hu et al, 2017; Jiang et al, 2019), DIC and TA data from 2006 to 2010 (Guo et al, 2012; Hu et al, 2014; Huang et al, 2015), and DIC and DO data from 2011 to 2016 (Wang et al, 2018).…”
Section: Methodsmentioning
confidence: 99%